Development and validation of the children’s filial behaviors scale - Kyeong, Yena (2024)
Filial care, encompassing respect and support for parents, is a fundamental value in many Asian families, shaping parent-child relationships throughout a child’s life. While extensively studied in adulthood, the development and socialization of filial care attitudes or behaviors in earlier developmental stages remain less explored. This study addresses this gap by creating and validating a developmentally sensitive assessment of filial care behaviors displayed in childhood and adolescence, which are not adequately captured by existing measures. Derived from a literature review, 12 items were generated to assess concrete filial care behaviors. A sample of 13-year-old children (n = 282) from Singapore’s birth cohort study reported on their filial care behaviors toward parents, along with other parent-child relationship variables. Parents (n = 278) also reported on their children’s filial care behaviors. Exploratory factor analyses yielded two factors in both samples: the Respect and Compliance (6 items; e.g., “I do what my parent(s) ask me to do right away”) and Affectionate Regard dimensions (4 items; e.g., “I let my parent(s) know I love them”). The two factors were significantly correlated, r = .68 in children and r = .55 in parents, with parent-child correlations ranging from .28 to .30. The scale demonstrated good reliabilities in both samples (Cronbach’s as > .76). It also displayed positive associations with perceived parental warmth and inverse associations with harsh parenting practices (i.e., physical discipline, psychological aggression), with slight variations in the extent across dimensions. This scale can serve as a useful tool for researching parent-child bonding during childhood and adolescence.